Challenges and opportunities in the establishment of a hereditary breast cancer clinic at an academic medical center in a low‐middle income country. Issue 4 (31st January 2022) - Ehsan, Lubaina; Waheed, Muhammad Talha; Akbar, Fizza; Siddiqui, Zahraa; Sattar, Abida K.; Kirmani, Salman
Abstract: It is now standard of care to offer genetic testing to patients at risk of hereditary breast cancer and make management decisions based on these results. Although great strides have been made in ensuring access to genetic testing and genetic counseling by establishing hereditary breast cancer clinics in well‐resourced countries, these are essentially non‐existent in low‐middle income countries like Pakistan. We established a hereditary breast cancer clinic involving a multidisciplinary team, including a medical geneticist and a genetic counselor. Our efforts were based on consensus guidelines and included educating medical providers about the importance of genetic testing in breast cancer care and the mandatory presence of a genetics team member at the weekly Breast Tumor Board meeting. This resulted in an increase in the number of referrals of breast cancer patients for genetic testing. In this report, we describe the challenges we faced in setting up such a system in Pakistan and the measures to overcome them. There is a need to establish such hereditary breast cancer clinics, which can also be replicated at other centers in low‐resource settings, to improve standardized assessment and management of the patients with hereditary breast cancer according to consensus guidelines.